Hidden forms : seeing and understanding things. - Clivio, Franco, ....-; Hansen, Hans, ....-; Mendell, Pierre, ....- (Basel : Birkhäuser, 2009)
The book Hidden Forms uses examples from Franco Clivio's collection of objects to reveal clearly and yet poetically the hidden qualities that require a practiced gaze. Working with ordinary, everyday, practical, seemingly design(er)less objects has been Franco Clivio's obsession both as a university lecturer and as a practicing designer. Each object in the collection stands for an unconventional, unconstrained, and sometimes unique solution to a problem that is often simple but always fundamental; fundamental in the sense of a design that places less emphasis on good form than on perfect function. A fruitful collaboration between Franco Clivio, the photographer Hans Hansen, and the graphic designer Pierre Mendell has produced a work that uses photographs, drawings, and texts to reveal the hidden qualities of objects for everyday use.